Surface waves in fibre-reinforced anisotropic solid elastic media under the influence of gravity - Sethi, Madhu; Gupta, Kishan Chand; Gupta, Deepak; Gupta, Manisha (Zielona Góra: Uniwersytet Zielonogórski)
The aim of the present paper is to investigate surface waves in an anisotropic, elastic solid medium under the influence of gravity. First, a theory of generalised surface waves was developed and then it was employed to investigate particular cases of waves, viz., Stoneley and Rayleigh, Love type. The wave velocity equations were obtained for different cases and they are in well agreement with the corresponding classical result, when the effect of gravity, viscosity as well as parameters for fibre-reinforcement of the material medium are ignored.
Keywords: fibre-reinforced medium; surface waves; viscosity; Rayleigh waves; gravity